Occurrence of Cochlochila bullita Stål in Malaysia - Tan, Li Peng; Ahmad Said Sajap,; Lee, Han Jeen; Lee, Seng Hua; Lum, Wei Chen (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2014)
The first occurrence of Lace bug, Cochlochila bullita Stål, was recorded in Malaysia in year of 2010. Description of this species was made. Damage on Ocimum basilicum and Orthosiphon aristatus caused by Cochlochila bullita Stål was investigated in this study. Symptoms of the infested plants were also described. Possible control method against this pest was also suggested.